Pengaruh Struktur Kepemilikan Dan Karakteristik CFO Terhadap Konservatisme Akuntansi - Peni Aliza; Vanica Serly (Universitas Negeri Padang, 2020)
In Indonesia, there are cases of failure in the application of accounting conservatism in manufacturing companies, one of which is PT. Tiga Pilar Sejahtera Food Tbk. which made a mistake in the presentation of financial statements. This error resulted in overstated profits in the year ended December 31, 2017. This indicates a failure in the application of accounting conservatism in manufacturing companies due to carelessness and management's interest in presenting financial statements, resulting in overstated net income. In this case, the company is considered to have excessive optimism in recognizing profit, which causes the value of profit to be greater than it should be. This study aims to see the effect of ownership structure and CFO characteristics on accounting conservatism in manufacturing companies listed on the Indonesia Stock Exchange for the period 2014-2018. This type of research is quantitative. The population used in this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX) with a total sample of 112 samples using purposive sampling method. The analysis was performed using multiple regression models. The results of this study indicate that: (1) Managerial ownership has a negative but insignificant effect on accounting conservatism with a significance level of 0.564. (2) Institutional ownership has a positive and significant effect on accounting conservatism with a significance level of 0.291. (3) The tenure of CFO has a positive and insignificant effect on accounting conservatism with a significance level of 0.804